Examining users’ trust in the travel information provided in social networking services (SNS) - Norbayah Mohd Suki,; Norazah Mohd Suki, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Research into the effect of users’ trust in social media for travel consumption remains unaddressed within tourism literature. Hence, the principal goal of this research is to examine factors influencing users’ trust in travel information provided in social networking services (SNS). Multiple regression analysis was the chosen method of data analysis to assess the hypothesized relationships. The findings revealed that users’ trust in travel information provided by SNS is heavily linked with perceived values. Users are heavily reliant on SNS as they consider SNS as reliable avenues to obtain recent travel information at anytime and anywhere to aid their decision making. At the same time, they are still concerned that their personal detailss are being misused by others without their consent. The quantitative results delivered instrumental understanding to the tourism-related organizations regarding the significant factors affecting users’ trust in travel information provided by SNS. It is vital for them to strongly uphold users’ trust the travel information by outlining effective marketing strategies and persuasive advertising campaigns regarding the companies’ travel products and services via the SNS which could trigger travel consumption and destination visit intentions and behaviours. Suggestion for future research is also presented.